Comparison of Early Childhood Asthenopia Levels Between Traditional Marsitekka or Engklek Guess The Picture Games and Digital Games - Siregar, Aisiyah Aminy; Diputera, Artha Mahindra; Br Tarigan, Evilyenta Kanani; Berutu, Nola Sonia; Br Lb, Elisa F.; Nasution, Masdaleni (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2024)
Gadgets it can be a problem when parents take the initiative to give gadgets to their children excessively which can result in Asthenopia (eye fatigue). The aim of this research is to find out how the level of asthenopia or eye fatigue in early childhood compares between the traditional game marsitekka or engklek GTP (Guess the Picture) and modern games. The research method used is experimental research using a mix method technique. Statistical tests use statistical analysis of the t test or difference test (t-test) and qualitative research is analyzed using Kohlberg theory. The results obtained is having an average difference with a value of 5,467. so this data shows that asthenopia in early childhood has a level of difference between traditional games and use of gadget set, with the level of asthenopia in traditional games being lower than in modern games. The impact of this research is expected to be one way to prevent the occurrence of Asthenopia in early childhood by developing traditional game models which are starting to be forgotten in the current technological era.